Impact of hydrogenation on miscibility of fast pyrolysis bio-oil with refinery fractions towards bio-oil refinery integration. (August 2021) - Dimitriadis, A.; Liakos, D.; Pfisterer, U.; Moustaka-Gouni, M.; Karonis, D.; Bezergianni, S.
Abstract: In particular, a straw-based Ablative Fast Pyrolysis (AFP) oil was upgraded via hydrotreatment (HDT) in order to be used as a blending component with fossil-based intermediates. The raw pyrolysis oil is characterized by H/C = 0.14, O/C = 0.58 and C = 57.73 wt%, while the HDT pyrolysis oil has a H/C = 0.14, O/C = 0.016 and C = 85.85 wt%. Based on the density, viscosity and composition, and in association with a typical refinery, the possible petroleum refinery entry points for HDT pyrolysis oil include Straight Run Gas-Oil (SRGO), Atmospheric Gas-oil (GO), Fluid Catalytic Cracking Light Cycle Oil (LCO) and Heavy Cycle Oil (HCO), as well as Light Vacuum Gas-Oil (LVGO). To that aim, this work examined raw and HDT bio-oil blends with the aforementioned candidate petroleum streams at a 30:70 v/v ratio (raw or HDT bio-oil/petroleum stream) with respect to their miscibility, by comparing the blend components' properties, microscopic observation, and interfacial tension analysis. From the microscopic observation, the addition of HDT pyrolysis oil in all examined petroleum candidates renders a homogeneous mixture where the two phases cannot be distinguished. In addition, no interfacial tension was observed in the examined blends, while the blend of HDT pyrolysis oil with the different petroleum streams not only did not deteriorate the fuel characteristics over the original petroleum stream, but also it improved them, in some cases. In general, the HDT pyrolysis oil was found to be miscible with all the examined refinery streams, extending the potential further investigation of stabilized pyrolysis oil integration over oil refineries. Graphical abstract: Image 1 Highlights: Raw pyrolysis bio-oil is not miscible with common petroleum streams. Pyrolysis oil miscibility is improved via hydrotreatment. Dissolved water affects homogeneity of binary blends. Most common petroleum streams are miscible with HDT pyrolysis oil. High viscosity petroleum streams blending with HDT pyrolysis oil favors flow properties.